Use of Mnemonic Products in Volume Unit Conversion Materials in Elementary Schools - Januar, Exsaris; Sahyuddin, Sahyuddin (Postgraduate School, Universitas Negeri Padang, 2024)
This study aimed to improve the numeracy literacy and learning outcomes of fifth-grade students at Sekolah Indonesia Kota Kinabalu (SIKK) in volume unit conversions through the innovative Demonic method, which combines Demonstration and Mnemonic techniques. Employing Classroom Action Research (CAR), the study was conducted in two cycles with 15 students during the 2023/2024 academic year. Data were collected through observations, interviews, and pre- and post-tests. Results showed a significant increase in the average test score from 64.04 in Cycle I to 90.57 in Cycle II, with the percentage of students achieving the Minimum Completion Criteria rising from 38% to 90%. The integration of Mnemonic strategies enhanced memory retention, while Demonstration methods supported active participation and hands-on learning. The study concludes that the Demonic method effectively addresses learning gaps and fosters better comprehension of volume unit conversions.